Strict Efficiency in Vector Optimization with Nearly Convexlike Set-Valued Maps - Xiaohong Hu; Zhimiao Fang; Yunxuan Xiong (Abstract and Applied Analysis)
The concept of the well posedness for a special scalar problem is linked with strictly efficient solutions of vector optimization problem involving nearly convexlike set-valued maps. Two scalarization theorems and two Lagrange multiplier theorems for strict efficiency in vector optimization involving nearly convexlike set-valued maps are established. A dual is proposed and duality results are obtained in terms of strictly efficient solutions. A new type of saddle point, called strict saddle point, of an appropriate set-valued Lagrange map is introduced and is used to characterize strict efficiency.